The Role of Accounting Fundamentals in Explaining Stock Returns: Case of Pakistan Stock Exchange (PSX) - Khadija Ashfaq; Dr. Abdul Raheman (Indus Journal of Social Sciences, 2025)
This study demonstrates that a firm's accounting variables have a considerable impact on stock price movements. This data is based on the Zhang model (Chen & Zhang 2007), which associates a firm's return with its underlying accounting measurements. Stock returns are estimated by combining four cashflow-based accounting indicators (earnings yield, growth potential, equity capital investment, and profitability) with one non-cashflow-based component (discount rate). The data was acquired from firms on the KSE-100 index. The relationships were analyzed using a fixed effect regression model with a time frame ranging from 2016 to 2023. The empirical findings of this study show that earning yield has a considerable positive impact on stock returns while discount rate has a significant negative impact.